Real-time haptic feedback system validity and its fesibility for runners in a real-world training environment - Wong, J.; Sheerin, K.; Wyatt, H. (ISBS Proceedings Archive (Michigan), 2021)
This study sought to assess the use of a novel integrated haptic feedback system for use during running; specifically, the study aimed to 1) assess the validity of the system in measuring trunk inclination and step rate during running and 2) assess the feasibility of the system to modify running technique in a real-world training environment. Ten recreational runners initially ran on an instrumented treadmill in a laboratory where trunk angle and step rate data were collected from an IMU-based system and compared against 3D motion capture and instrumented treadmill data. Participants then completed three outdoor training sessions using the haptic system to modify step rate. The haptic system was found to be valid when compared to gold-standard laboratory methods for measuring step rate (max 1.1% difference). It was also found to be feasible and intuitive in providing real-time feedback via a vibrating wrist-mounted unit in a real-world training environment. Overall, the system showed promise for application to real-world gait retraining, however further refinements are needed to improve the validity of trunk inclination measurements.